Uma guerra sangrenta, epidêmica e doente: espaços de cura e cotidiano médico na guerra do Paraguai (1864 – 1870) - Barbosa, Janyne Paula Pereira Leite (2018)
The long duration of the Paraguayan War (1864-1870), analyzed through travel journals, official correspondence and documentation relating to the period, brutally exposes the treatment given to soldiers, civilians and other participants who fought in the war against the common enemy, Paraguay. Allied forces, Argentines, Uruguayans and Brazilians, fought above all for survival on battlefields characterized by lack of potable water, insufficient and unfit food, corpses heaped in the open air, and the absence of medical instruments to treat patients. All these factors have raised hypotheses about new interpretations that must be given to the War regarding the daily aspects and the survival of the troops and the civilian population. With the outbreak of the war, the country began a period of reorganization of Army forces, including the Army's Health Corps in order to send forces to the front. In this way, our goal was to understand the daily life of healing spaces that worked during the conflict, including the practice of medical practice and the struggle for survival by civilians and the sick. For this, this work dialogues with a diversified documentary corpus aiming to give new meanings to the greatest military conflict experienced by Brazil. We conducted the research under the New Cultural History approach in dialogue with the History of health and diseases, worrying about new interpretations, with conscious actions or not, with the places and the daily life of the sick and wounded, in the attempt to give new approaches to the issues surrounding the Paraguayan War. Therefore, our work is part of the History and Regionalities line, dialoguing with diverse aspects of the daily life of the military and civilians during the conflict in the south of the country.